2014
DOI: 10.2478/jomb-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridamole Stress Echocardiography Does Not Trigger Release of Highly-Sensitive Troponin I and T

Abstract: SummaryBackground: The patients with episodes of chest pain and no electrocardiographic or biomarker abnormalities are currently monitored and subjected to non-invasive testing. Stress echocardiography is one of the most often used provocative tests, being the most cost-and risk-effective imaging technique. Some concerns about this technique have been raised regarding potential drug-induced myocardial injury. Our study hence aimed to establish whether or not dipyridamole stress echocardiography elicits release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…One included 125 consecutive blood donors who participated in the definition of the local reference range for the cTnI immunoassay, as described elsewhere ( 13 ). The other population (i.e., ED patients with no trauma) consisted of 25 consecutive patients admitted to the local observation unit for evaluation of chest pain at moderate-to-high probability, who had negative results of dipyridamole-atropine echocardiography, as also described elsewhere ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…One included 125 consecutive blood donors who participated in the definition of the local reference range for the cTnI immunoassay, as described elsewhere ( 13 ). The other population (i.e., ED patients with no trauma) consisted of 25 consecutive patients admitted to the local observation unit for evaluation of chest pain at moderate-to-high probability, who had negative results of dipyridamole-atropine echocardiography, as also described elsewhere ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…48 Our findings in the DIP group are consistent with previously published studies showing no hsTnT release following a dipyridamole challenge, which is probably due to the absence of adrenergic stimulation and resulting increased wall stress observed during the ExSE and DSE. 15,16,49,50…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to previously published studies. [9][10][11][12][13][14][15][16][17] During the study enrolment period, CTAg was not available in our hospital, and performing invasive coronary angiograms on patients with a low PTP of obstructive IHD with a negative result of SE, was not found to being justifiable. On the other hand, all stress echo modalities are reported to have similar levels of accuracy and sensitivity 4 which is a potential mechanism behind the increase in hsTnT, was not systematically studied.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported all AEs regardless of their severity. In the literature, we found reports of the occurrence of AE after intravenous administration of dipyridamole in 40 to nearly 70% of patients [19,20].…”
Section: Discussionmentioning
confidence: 99%